THE CHINESE COMMUNIST PARTY ELITE AND THEIR INFLUENCE ON CHINA’S FOREIGN POLICY - A’zamov Sobirkhuja Sobitkhan o’g’li (Modern American Journals, 2025)
This essay examines the dominant role of the Chinese Communist Party (CCP) elite in shaping China’s foreign policy. It explores how centralized authority—especially under Xi Jinping—has enabled a cohesive yet rigid approach to international affairs. The CCP elite influence key foreign policy areas such as relations with the United States, Taiwan, and the Belt and Road Initiative through strategic control, ideological framing, and long-term planning. While this centralized model provides policy consistency, it also limits flexibility and adaptability in global diplomacy. Understanding the structure and mindset of the CCP elite is essential for interpreting China’s foreign policy behavior in today’s multipolar world.
Keywords: Chinese Communist Party (CCP), General Secretary, People’s Liberation Army (PLA), the Ministry of Commerce, Foreign Policy, issues, BRI, Global South, “Wolf Warrior” diplomacy.